Characterization and Control of Pore Structural Heterogeneity for Low-Thermal-Maturity Shale: A Case Study of the Shanxi Formation in the Northeast Zhoukou Depression, Southern North China Basin - Liu, Enran; Liu, Chenglin; Shi, Dishi; Zhu, Disi; Xu, Qiuchen; Wang, Yanhong (Frontiers in Earth Science, 2022)
The Shanxi Formation in the northeast of Zhoukou Depression, Southern North China Basin, mainly consists of interbed layers of dark mudstone and widely developed coal, which is a promising target for unconventional oil and gas exploration. A series of geochemical and geological methods were used to analyse the characterization and controls of the pores structural heterogeneity in low thermal maturity shale. These methods include Rock-Eval analyses, total organic content, Scanning electron microscope observation with energy-dispersive spectrometer (SEM-EDS), X-ray diffraction and low-pressure N2 adsorption. Based on these data, the pore di-ameter and fractal dimension were calculated, the pore structure and fractal dimension characteristics of low maturity shale were analyzed. The average of micropore and macropore fractal dimension is both 2.77, but the average of mesopore is 2.65, indicating a more complex pores structure for micropore and macropore than the mesopore. The S2, a parameter of Rock-Eval analyses, has a positive correlation with the specific surface area, but the S1 and TOC both have no clear correlation with that, indicating an increase effect of kerogen on the specific surface area. Moreover, the organic matter existed in pores shows no clear correlation with the fractal dimensions, which means no effect on pore structural heterogeneity. Quartz and clay minerals have no clear correlation with the fractal dimensions, and so do not affect the pore structural heterogeneity. Illite (It) has a strong correlation with the fractal dimensions, which means a strong role in lowering to the pore structural heterogeneity.